2023
DOI: 10.1186/s40345-023-00288-6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the effectiveness of dialectical behavior therapy for improving mood symptoms in bipolar disorders

Abstract: Background Evidence-based psychotherapies available to treat patients with bipolar disorders (BD) are limited. Dialectical behavior therapy (DBT) may target several common symptoms of BD. We conducted a systematic review on the efficacy of DBT for mood symptoms in patients with BD. The systematic search used key words related to DBT and BD in Medline, Embase, PsycInfo, CINAHL, and Cochrane Library databases from 1980 to April 1st, 2022. We included studies that enrolled patients with a BD I or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…The results indicated that DBT effectively reduces impulsivity, improves emotion regulation, decreases rumination, and lessens self-criticism in individuals with trichotillomania. These findings are consistent with the previous research (20,(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 94%
“…The results indicated that DBT effectively reduces impulsivity, improves emotion regulation, decreases rumination, and lessens self-criticism in individuals with trichotillomania. These findings are consistent with the previous research (20,(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 94%